COMPARISON OF LIGHT QUARK AND CHARM QUARK FRAGMENTATION - Kesten, P; Akerlof, C; Bonvicini, G; Chapman, J; Errede, D; Harnew, N; Meyer, D; Nitz, D; Seidl, A; Thun, R; Trinko, T; Willutzky, M; et al. (1985)
Separate samples of charm quark and light quark (u, d, s) jets have been isolated in an experiment studying e+e- annihilations at s = 29 GeV. The results come from data corresponding to an integrated luminosity of 111 pb-1 collected by the High Resolution Spectrometer. Differences were observed in charged multiplicities, momentum distributions, and rapidity of the size expected from the different fragmentation functions and leading particle decay properties of the two samples. © 1985.